Towards Enhanced Galactose Utilization by Lactococcus lactis - Neves, Ana R. (American Society for Microbiology (ASM), 2010)
Accumulation of galactose in dairy products due to partial lactose fermentation by lactic acid bacteria yields poor-quality products and precludes their consumption by individuals suffering from galactosemia. This study aimed at extending our knowledge of galactose metabolism in Lactococcus lactis, with the final goal of tailoring strains for enhanced galactose consumption. We used directed genetically engineered strains to examine galactose utilization in strain NZ9000 via the chromosomal Leloir pathway (gal genes) or the plasmid-encoded tagatose 6-phosphate (Tag6P) pathway (lac genes). Galactokinase (GalK), but not galactose permease (GalP), is essential for growth on galactose. This finding led to the discovery of an alternative route, comprising a galactose phosphotransferase system (PTS) and a phosphatase, for galactose dissimilation in NZ9000. Introduction of the Tag6P pathway in a galPMK mutant restored the ability to metabolize galactose but did not sustain growth on this sugar. The latter strain was used to prove that lacFE, encoding the lactose PTS, is necessary for galactose metabolism, thus implicating this transporter in galactose uptake. Both PTS transporters have a low affinity for galactose, while GalP displays a high affinity for the sugar. Furthermore, the GalP/Leloir route supported the highest galactose consumption rate. To further increase this rate, we overexpressed galPMKT, but this led to a substantial accumulation of α-galactose 1-phosphate and α-glucose 1-phosphate, pointing to a bottleneck at the level of α-phosphoglucomutase. Overexpression of a gene encoding α-phosphoglucomutase alone or in combination with gal genes yielded strains with galactose consumption rates enhanced up to 50% relative to that of NZ9000. Approaches to further improve galactose metabolism are discussed.